Encapsulation of Chaotropic closo‐Decahydrodecaborate Clusters Within Cyclodextrins: Synthesis, Solution Studies, and DFT Calculations. Issue 29 (18th July 2019) - Diab, Manal; Floquet, Sébastien; Haouas, Mohamed; Abramov, Pavel A.; López, Xavier; Landy, David; Damond, Aurélie; Falaise, Clément; Guérineau, Vincent; Touboul, David; Naoufal, Daoud; Cadot, Emmanuel
Abstract : This paper deals with the formation of host‐guest systems between cyclodextrins and the closo ‐decahydrodecaborate cluster. The inclusion processes, although involving weak interaction, were evidenced in solution by ESI‐MS and various NMR techniques. ITC measurements provided thermodynamic parameters, and DFT calculations gave some elements that help in understanding these processes. Abstract : This paper deals with the encapsulation process of the cluster [B10 H10 ] 2– within cyclodextrins. This process was investigated in solution by ES‐MS, NMR, and ITC while DFT calculations bring theoretical support. It reveals that, even if the association constant is relatively low, the cluster [B10 H10 ] 2– can enter as a new member in the family of chaotropic clusters.